Contexts of physical therapy in the care of pregnant women during labor: integrative review (Research, Society and Development, 2022)
This study aimed to discuss the contexts of physical therapy in the care of pregnant women throughout the prepartum period. The current professional assistance to pregnant women is often organized according to the needs of the institutions and not the parturients, and therefore often requires attitudes and procedures that prioritize the quality of care, going beyond the model of care focused only on monitoring and risk control. The study is a descriptive study made from an integrative literature review in the LILACS, MEDLINE, PubMed, and SciELO databases, with 8 articles selected by the inclusion criteria, from 2017 to 2022. Obstetric Physiotherapy proved to be relevant as a support to the parturient woman, where it evidenced the positive influence of the mobility of the pregnant woman during labor, with the acquisition of vertical postures, diaphragm coordination, ambulation, pelvic movement and relaxation of the perineum, besides the reduction of discomforts and prevention of complications. In view of the above one can see that the presence of the physical therapy professional is of crucial importance throughout the woman's entire gravidic-puerperal process.